2016
DOI: 10.1111/nph.14210
|View full text |Cite
|
Sign up to set email alerts
|

Trading direct for indirect defense? Phytochrome B inactivation in tomato attenuates direct anti‐herbivore defenses whilst enhancing volatile‐mediated attraction of predators

Abstract: Under conditions of competition for light, which lead to the inactivation of the photoreceptor phytochrome B (phyB), the growth of shade-intolerant plants is promoted and the accumulation of direct anti-herbivore defenses is down-regulated. Little is known about the effects of phyB on emissions of volatile organic compounds (VOCs), which play a major role as informational cues in indirect defense. We investigated the effects of phyB on direct and indirect defenses in tomato (Solanum lycopersicum) using two com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
98
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(164 citation statements)
references
References 114 publications
7
98
0
4
Order By: Relevance
“…A recent study suggested that shifts in the blend of VOCs induced by phyB inactivation could play an important role in the attraction of predatory insects. Working with tomato, Cortés et al () found that when phyB was inactivated (by mutation or supplemental FR), leaf defenses were down‐regulated, as expected; however, at the same time, phyB inactivation led the plants to produce a blend of JA‐induced monoterpenes that increased their attractiveness to the predatory mirid bug Macrolopus pigmaeus (Cortés et al ). This predator can provide indirect protection to tomato plants by feeding on their insect herbivores (Lins et al ).…”
Section: Growth‐defence Balancementioning
confidence: 82%
“…A recent study suggested that shifts in the blend of VOCs induced by phyB inactivation could play an important role in the attraction of predatory insects. Working with tomato, Cortés et al () found that when phyB was inactivated (by mutation or supplemental FR), leaf defenses were down‐regulated, as expected; however, at the same time, phyB inactivation led the plants to produce a blend of JA‐induced monoterpenes that increased their attractiveness to the predatory mirid bug Macrolopus pigmaeus (Cortés et al ). This predator can provide indirect protection to tomato plants by feeding on their insect herbivores (Lins et al ).…”
Section: Growth‐defence Balancementioning
confidence: 82%
“…Similarly, no information currently exists on the effects of LED lights on the biology of A. aphidimyza . LED lights are now being widely adopted in the greenhouse industry and are known to affect lifetable characteristics and interactions between plants other natural enemy species …”
Section: Aphidoletes Aphidimyza As Biocontrol Agentmentioning
confidence: 99%
“…LED lights are now being widely adopted in the greenhouse industry and are known to affect lifetable characteristics and interactions between plants other natural enemy species. 101 Conditions inducing diapause (Section 2.3.4), namely photoperiod, have been mentioned as a cause of reduced efficacy of A. aphidimyza in the crop. 59,71 The occurrence of diapause at short daylengths in this biocontrol agent is a significant barrier to its year-round use for aphid control by growers.…”
Section: Climate and Cropping Systemmentioning
confidence: 99%
“…Many OMCL groups with possible functions in the JA-mediated defense against herbivores or necrotrophic pathogens appeared to be downregulated after 11.5 h of low R:FR treatment in G. pyrenaicum, but not, or to a lesser extent, in G. robertianum ( Figure 4B; Supplemental Figure 5A). Downregulation of defense pathways by low R:FR has also been described in Arabidopsis (Cargnel et al, 2014;Cerrudo et al, 2012;de Wit et al, 2013) and tomato (Cortés et al, 2016). Geranium orthologs of JA-inducible genes JASMONIC ACID RESPONSIVE3 (JR3), TRANSPARENT TESTA7 (TT7), and PRODUCTION OF ANTHOCYANIN PIGMENT1 (PAP1) were transcriptionally induced by a methyl-JA treatment, but this induction was suppressed by simultaneous exposure to low R:FR light in G. pyrenaicum ( Figure 4C (A) Heat map of the gene ontology clusters overrepresenting transcripts with a positive species*treatment interaction (log 2 fold changes are significantly higher in G. robertianum compared with G. pyrenaicum) at t = 11.5 h, and a role in plant defenses against pests.…”
Section: Ja-mediated Defenses Are Repressed By Low R:fr In G Pyrenaimentioning
confidence: 99%